DYSLIPIDEMIA AMONG SMOKERS - Sharma, Preeti; Kumar, Pradeep; Sharma, Rachna; K, Kishor; G, Gupta (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The objective of this study is to evaluate lipid profile among cigarette smokers and compare it with non-smokers. Methods: About 125 subjects aged between 20 and 40 years including 100 smokers as case group and 25 non-smokers as control were taken into study. They did not having any history of any disease (i.e., diabetes, hypertension, liver diseases, renal diseases, or obesity) or alcohol intake. They were not taking any drug such as B-blockers, lipid lowering drugs, or thiazide diuretics. Results: The mean serum total cholesterol, low-density lipoprotein cholesterol (LDL-C), very LDL-C (VLDL-C) were significantly raised (p<0.05) in all three groups of mild, moderate, and heavy smokers as compared to non-smokers control while mean serum high--density lipoproteins cholesterol (HDL-C) was significantly lower in all three above said groups. Conclusion: Cigarette/beedi smoking is associated with lower level of god cholesterol, i.e., HDL, and higher level of cholesterol, triglycerides, and serum LDL and VLDL. Keywords: Dyslipidemia, smokers